Synthesis of 1, 1′‐ and 2, 2′‐Bicarbazole Alkaloids by Iron(III)‐Catalyzed Oxidative Coupling of 2‐ and 1‐Hydroxycarbazoles1. Issue 2 (4th December 2017) - Brütting, Christian; Fritsche, Raphael F.; Kutz, Sebastian K.; Börger, Carsten; Schmidt, Arndt W.; Kataeva, Olga; Knölker, Hans‐Joachim
Abstract: We describe the synthesis of 1, 1′‐ and 2, 2′‐bicarbazoles by oxidative homocoupling of 2‐ and 1‐hydroxycarbazoles. The oxidative coupling using catalytic amounts of F16 PcFe can be applied to both groups of substrates. Although F16 PcFe generally provides the best yields for the synthesis of 1, 1′‐bicarbazoles, di‐ tert ‐butyl peroxide affords better results for the 2, 2′‐bicarbazoles. In our study, we have achieved the first syntheses of the biscarbalexines A–C, bisglybomine B, 2, 2′‐dihydroxy‐7, 7′‐dimethoxy‐3, 3′‐dimethyl‐1, 1′‐bicarbazole, bispyrayafoline C, and bisisomahanine. The iron‐catalyzed coupling of koenigine led to an improved synthesis of 8, 8′′‐biskoenigine and afforded an unprecedented decacylic product. Oxidative coupling of 1‐hydroxycarbazoles led to bisclausenol, and to the first total syntheses of bismurrayafoline B and D. Abstract : Iron catalysis : The iron‐catalyzed oxidative homocoupling of hydroxycarbazoles to bicarbazoles using hexadecafluorophthalocyanine‐iron in the presence of air has been investigated and compared to other methods for biaryl coupling.